Vaginal Birth After Cesarean: Neonatal Outcomes and United States Birth Setting. Issue 1 (March 2018) - Tilden, E.L.; Cheyney, M.; Guise, J.M.; Emeis, C.; Lapidus, J.; Biel, F.M.; Wiedrick, J.; Snowden, J.M.
Abstract : ( Am J Obstet Gynecol . 2017;216(4):403.e1–403.e8) Many hospitals are not willing to let a woman try to deliver vaginally if she has previously had a cesarean delivery (CD). As a result, women with prior CDs who want to avoid a second CD increasingly seek to have vaginal deliveries in free standing birthing centers or at home. This retrospective analysis of records for US births from 2007 to 2010 compared vaginal births occurring in a hospital setting with those occurring outside of hospitals in women who had previously had a CD. Statistical analysis was limited to singleton, full term live births with vertex presentation. Unadjusted, absolute and relative risk differences for different birth settings were calculated, and multivariate regression analyses were performed.